„Historia nie jest osobna”. Hannah Arendt i jej biografia/e - Nowicka, Daria (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
This article – as mentioned in the introduction – details three ways to understand the category of biography in Hannah Arendt’s writings. In the first, I mention the very act of writing a biography by the author – a story of Rahel Varnhagen or Walter Benjamin, also referring to the biographical and epistolographic essays that Arendt pointed out. In the second, I’m interested in the aspect of refugee biography proposed by Arendt in “We Refugees” which she used to redefine the term “refugee”. In the third aspect, I present Arendt as the protagonist of a biography in Julia Kristeva’s writings.